BRAND POSITIONING STRATEGY THROUGH DIGITAL MARKETING OF COMMERCIAL RICE PRODUCTS AT PERUM BULOG JEMBER BRANCH - Wibowo, Yuli; Purnomo, Bambang Herry; Salsabila (Jurnal Teknologi Industri Pertanian, 2024)
The development of information technology, especially in digital marketing, has brought significant changes in how companies interact with consumers and build company brand images, including Perum BULOG Jember Branch. This research aims to increase awareness of the "Beras Kita" brand as BULOG's premium rice product and strengthen the brand's position in the minds of consumers with a brand positioning strategy that includes designing a visual identity, namely designing a new logo and tagline, as well as through a digital marketing strategy for premium rice products. premium at Perum BULOG Jember Branch. This research uses the ME-MCDM (Multi-Expert Multi-Criteria Decision Making) method for selecting logos and taglines and the AHP (Analytical Hierarchy Process) method to determine digital marketing strategy priorities. The recommended digital marketing strategy, which has the highest priority, is using local influencers. Implementing this strategy is expected to improve the unfavorable brand image and strengthen the position of the "Beras Kita" brand in the market. Keywords: AHP, beras kita, brand positioning, digital marketing, MEMCDM, Perum BULOG